The effects of mTOR inhibition in ischemic stroke - Schneider, AM (2022)
With a global incidence of 9.5 million cases annually and 56 million disability-adjusted life-years, ischemic stroke is the primary cause of adult disability in developed countries. However, the significant successes in stroke trials have been in the field of reperfusion therapies for ischemic stroke, whereas clinical trials focusing on amplifying the brain’s intrinsic neuroprotective pathways have so far been unsuccessful for numerous reasons. One neuroprotective target that has been shown to play an essential role in cell death after stroke is the mammalian target of rapamycin complex 1 (mTORC1), a key regulator of the cells' energy supply, which can be modulated pharmacologically through rapamycin and non-pharmacologically through dietary intervention. The overarching aim of this thesis was to investigate the therapeutic potential of mTOR inhibition in ischemia. I found that post-stroke rapamycin treatment improves cerebral perfusion in the hyperacute phase, decreases lesion volume, and improves functional outcomes at three days in a rat model of focal stroke using magnetic resonance imaging. I then showed that rapamycin application after oxygen-glucose deprivation improves the function of pericytes and endothelial cells in vitro but does not prevent cell death. Finally, I found that fasting following ischemia might be an alternative strategy to improve stroke outcomes by decreasing inflammation, stabilizing the BBB, and reducing stroke volume. Together, these data highlight the potential of therapeutic options beyond reperfusion therapies and suggest that targeting metabolic regulators such as the mTOR pathway using pharmacology or dietary modulation might be effective adjunct therapy options alongside reperfusion for patients suffering from an ischemic stroke.